2017
DOI: 10.1111/imj.13549
|View full text |Cite
|
Sign up to set email alerts
|

Association between non‐alcoholic fatty liver disease and peripheral artery disease in patients with type 2 diabetes

Abstract: Type 2 diabetes patients with NAFLD had a higher prevalence of PAD, and this association was partly, but not entirely, explained by metabolic risk factors and inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“… 36,42‐46 Presence of NAFLD was associated with higher prevalence of both coronary heart disease (26.6% vs 18.3%) and cerebrovascular disease (20.0% vs 13.3%), as well as of peripheral arterial disease (15.4% vs 10.0%), in a study of 2839 outpatient T2DM patients 43 . Other groups have reported similar results indicating that NAFLD associated with higher prevalence of markers of advanced atherosclerotic lesions in major arteries, and their clinical manifestations 47‐49 . There is not substantial data yet indicating a preferential location of atherosclerotic lesions in patients with T2DM‐NAFLD.…”
Section: Is Nafld In Type 2 Diabetes Mellitus (T2dm) a Serious Healthmentioning
confidence: 89%
“… 36,42‐46 Presence of NAFLD was associated with higher prevalence of both coronary heart disease (26.6% vs 18.3%) and cerebrovascular disease (20.0% vs 13.3%), as well as of peripheral arterial disease (15.4% vs 10.0%), in a study of 2839 outpatient T2DM patients 43 . Other groups have reported similar results indicating that NAFLD associated with higher prevalence of markers of advanced atherosclerotic lesions in major arteries, and their clinical manifestations 47‐49 . There is not substantial data yet indicating a preferential location of atherosclerotic lesions in patients with T2DM‐NAFLD.…”
Section: Is Nafld In Type 2 Diabetes Mellitus (T2dm) a Serious Healthmentioning
confidence: 89%
“…Asymptomatic liver fibrosis has been shown to occur in approximately 5.4% of the general population [6]. However, the prevalence of liver disease was found to be much higher (63.0-69.2%) among patients with atherosclerotic vascular diseases [19,20]. Previous reports demonstrated that 23.0-42.7% of stroke patients had NAFLD according to laboratory results or abdominal sonography [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with T2D will worsen the course of NAFLD and, conversely, patients with NAFLD were at higher risk for cardiovascular complications of T2D [49]. In a cross-sectional study on 2,646 T2D patients, patients with NAFLD had significantly higher prevalence of PAD compared with those without NAFLD; this association was much stronger among women than among men [50]. Further studies are needed to screen for hepatic steatosis with/without fibrosis even with non-invasive tests [51].…”
Section: Co-morbiditiesmentioning
confidence: 96%